Models of parliamentary scrutiny of the quality of legislation. How different drafting models and forms of government shape them - Albanesi, Enrico (Theory and practice of legislation (Oxford, England), 2021)
The aim of this article is to set the scene for the following special issue, which contains four papers relating to research on parliamentary scrutiny of the quality of legislation in different jurisdictions. In Continental Europe, Parliaments (although in a rather different range: more in countries such as Italy and Spain, less in countries such as Germany) have developed a more-in-depth approach in scrutinising the quality of legislation, i.e. a set of tools, standards and bodies to scrutinise it downstream, than that of Westminster jurisdictions. In the latter, a high-standard quality of legislation is guaranteed upstream by having bills drafted by Parliamentary Counsel, although in the United Kingdom there is currently a debate concerning the opportunity to strengthen parliamentary scrutiny of the quality of legislation. The hypotheses of this research were that the aforementioned models of parliamentary scrutiny are differently shaped in those jurisdictions due to the drafting model and the form of government established there. Against this background, the United States Congress is a very different animal: due to the peculiarities of the legislative process in the presidential system, the scrutiny in Congress relies on multiple parties. The reason why articles have been commissioned here is to test now on a larger scale the aforementioned hypotheses, which have already been partially proved in a previous article mainly concerning Italy (E. Albanesi, 'Parliamentary Scrutiny of the Quality of Legislation within Europe' (2021) Statute Law Review). This time the analysis will focus on two Continental European parliamentary systems (Spain and Germany), one jurisdiction belonging to the Parliamentary Counsel/Westminster model (Canada) and one presidential system (the U.S.). The articles published here seem to support on a larger scale the aforementioned hypotheses. The article on Canada also helps reflect upon the opportunity to strengthen parliamentary scrutiny of the quality of legislation in Westminster jurisdictions.